In praise of bacteria : notes toward biotic architecture / Beatriz Colomina, Mark Wigley. - Colomina, Beatriz; Wigley, Mark (Lars Muller Publishers, 2025)
An urgent manifesto for an alternative architectural philosophy, this sequel to 'Are We Human?', treats bacteria as the real architects, construction workers, maintenance crews and inhabitants of buildings. Colomina and Wigley draw on the latest research into microbes to rethink the past and possible futures of the built environment. The book explores the intimate entanglements of the microbes within bodies and buildings over the last 10,000 years, culminating in the antibiotic philosophy of contemporary architecture.